Simulation and development of ZigBee based wireless stakeout system controlled by PC - Sarwar, M.B. (Institute of Electrical and Electronics Engineers Inc., 2015)
Wireless technology has become a new emerging technology in stakeout and security concerns industries. Study of wireless communication with energy efficiency is also a one of the most important research area. Therefore this paper presents an efficient computerized stakeout system (CSS) for stakeout and recognition purposes with the use of energy efficient ZigBee based transceiver. The designed model entails a combination of programmable microcontrollers, relay circuitry, DC motors and sharp camera eye to control the model through another wireless transceiver module which is connected with personal computer. In the operation of each sensor node in wireless and movable stakeout system, battery is also a most limiting factor for the whole system performance and lifetime so it is obtained that ZigBee transponders are capable in providing wider transmission range and efficient compare to RF and Wi-Fi due to low usage of power during data gathering transmission. The computer commands are used to control the motion and visual feedback is used to provide the precision control. The CSS system is capable of positioning at tedious and hazardous work space as instructed through command to get the actual visual feedback. The results are in good agreement with theoretical understandings and show a greater efficiency, with low power consumption and reduction in complexity. Â© 2015 IEEE.